2015
DOI: 10.1007/s00384-015-2169-y
|View full text |Cite
|
Sign up to set email alerts
|

Dynamic magnetic resonance imaging evaluation of pelvic reconstruction with porcine dermal collagen mesh following extra-levator abdominoperineal excision for primary rectal cancer

Abstract: The implantation of a porcine dermal collagen mesh is an effective and reliable option for pelvic floor reconstruction after extra-levator abdominoperineal excision. Despite a high incidence of primary wound infections, the healing rate was satisfactory, no mesh had to be removed, and long-term stability could be achieved.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

1
11
0

Year Published

2016
2016
2019
2019

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 6 publications
(12 citation statements)
references
References 32 publications
1
11
0
Order By: Relevance
“…Fifteen studies were identified through the literature search [11,12,[34][35][36][37][38][39][40][41][42][43][44][45][46], reporting on 451 patients who underwent mesh reconstruction of the perineum following ELAPE, including 81 patients from two RCTs that compared mesh with primary closure [11,12]. Results of these studies are summarised in Table 4.…”
Section: Elape -Mesh Closurementioning
confidence: 99%
“…Fifteen studies were identified through the literature search [11,12,[34][35][36][37][38][39][40][41][42][43][44][45][46], reporting on 451 patients who underwent mesh reconstruction of the perineum following ELAPE, including 81 patients from two RCTs that compared mesh with primary closure [11,12]. Results of these studies are summarised in Table 4.…”
Section: Elape -Mesh Closurementioning
confidence: 99%
“…Dynamic MRI was performed 12 months after the eLAPE procedure The cine MRI sequence was a T2weighted TrueFISP (True fast imaging with steady state precession) of a single, 10 mm slice, repeated at sub 0.5 s intervals to give a 'CINE' loop, and was acquired when the patient was asked to strain, thus demonstrating an active Valsalva manoeuvre [1]. T2-weighted sagittal and coronal views were obtained at rest in the supine position with the patient performing a Valsalva manoeuvre flowed by imaging at rest, when the patient was not performing a Valsalva manoeuvre [2,3].…”
Section: Supporting Informationmentioning
confidence: 99%
“…Many techniques have been described to solve the difficulty of rectal division [1,2], but classical options such as rectal eversion should not be forgotten. Eversion of the anal canal and rectal stump after division of the colon at a higher level was employed to perform proctocolectomy with handsewn ileoanal pouch anastomosis [3,4]. This technique, often using a curved circular stapler, can be invaluable in performing a sphinctersaving operation in colorectal surgery [5].…”
Section: Supporting Informationmentioning
confidence: 99%
See 2 more Smart Citations